Models and policies for family development, population control, and family planning: a scoping review - Astuti, Dhesi Ari; Hasibuan, Khoirunnisah; Realita, Friska; Hisan, Urfa Khairatun (International Journal of Public Health Science (IJPHS), 2024)
Uncontrolled population growth causes poverty, hunger, disease and death. Ironically, population explosions usually occur in developing countries, while population growth is usually low, zero, or even negative in developed countries. Considering these factors, this research aims to formulate effective family planning and population control methods to improve the quality of family development. In this research we present a scoping review article regarding family development models and policies, population control, and family planning. A comprehensive search was conducted in major databases, including PubMed, EBSCO, ProQuest, and ScienceDirect, via presentation methods using PRISMA-ScR guidelines. As a result, we found 16 articles meeting the eligibility criteria. The findings of this research provide insight to stakeholders and researchers into how family development, population control, and family planning policies can be modeled so that effective results can be achieved.